Exploring Teachers’ Written Corrective Feedback on Students’ Writing Assignment at Junior and Senior High Schools: A Descriptive Study at SMP Negeri 22 Padang and SMA Negeri 12 Padang - Hijriani, Dini; Hamzah, Hamzah (Journal of English Language Teaching, 2024)
This study intended to figure out the types of English teachers’ written corrective feedback, the techniques used and the challenges faced by English teachers when giving written corrective feedback. This study was descriptive research. A total of four English teachers from SMP Negeri 22 Padang and SMA Negeri 12 Padang were selected by maximal variation sampling. Students’ writing assignment and interview were used as instruments to collect data. Students’ writing assignments were used to figure out what kinds of written corrective feedback and techniques that teachers used when giving feedback, while interview were used to figure out what challenges that teachers faced when giving written corrective feedback on students’ writing assignment. According to the study’s findings, English teachers at SMP Negeri 22 Padang and SMA Negeri 12 Padang only used two forms of written corrective feedback. They were direct corrective feedback and indirect corrective feedback. Then, English teachers’ techniques when giving written corrective feedback were adding, deleting, substituting, circling, commenting, crossing out, questioning, moving around, and underlining. Last, the challenges that English teachers faced when giving written corrective feedback were limited time, students’ attitude, students’ proficiency, and students’ handwriting.